2013
DOI: 10.1161/circulationaha.112.110056
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Pathology Determines Midterm Outcome After Endovascular Repair of the Thoracic Aorta

Abstract: Given the spectrum of different pathologies that affect the descending thoracic aorta, it is important to define whether the outcome of TEVAR is pathology specific to refine procedural technique and endograft design. Careful analysis of long-term Background-Endovascular repair of the thoracic aorta has become an increasingly utilized therapy. Although the shortterm mortality advantage over open surgery is well documented, late mortality and the impact of presenting pathology on long-term outcomes remain poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(56 citation statements)
references
References 34 publications
3
46
0
3
Order By: Relevance
“…Although TEVAR had the advantages of lower perioperative morbidity and mortality for type B aortic dissection, the advantages seemed to depend on a high rate of reintervention. Previous study reported that more than 20% of patients needed reintervention at 1-year after TEVAR (5) and the number reached up to 54% at 6-year (6).…”
mentioning
confidence: 93%
“…Although TEVAR had the advantages of lower perioperative morbidity and mortality for type B aortic dissection, the advantages seemed to depend on a high rate of reintervention. Previous study reported that more than 20% of patients needed reintervention at 1-year after TEVAR (5) and the number reached up to 54% at 6-year (6).…”
mentioning
confidence: 93%
“…3 Prospective registries in the endovascular management of other uncommon aortic diseases, including thoracic aortic dissection and aneurysm, have proven utility. 4,5 However, there are major drawbacks with such registries, including reporting bias, missing data, and selective loss to follow-up. Retrospective registries have additional limitations.…”
Section: Article See P 2136mentioning
confidence: 99%
“…7,8 Although the use of TEVR as a definitive treatment for either acute 9 or chronic 10 aortic dissection remains controversial, its use in emergent, complicated cases of acute DeBakey type III aortic dissection is generally considered acceptable and potentially lifesaving; in fact, in many programs, TEVR has become the treatment of choice for such cases. 11 Patterson and colleagues 12 are to be commended for reporting outcomes from one of the largest nonadministrative series of TEVRs (n=1010) in the current issue of From the 1010 patients in the series, the authors selected all those treated for aneurysm (n=670), chronic dissection (>2 weeks since onset; n=195), or acute dissection (≤2 weeks since onset; n=114), so the study cohort comprised 979 patients. In the analysis, patients were stratified according to their presenting pathology.…”
Section: Article See P 24mentioning
confidence: 99%
“…Additionally, such analysis is important in light of the disappointing long-term results of abdominal endovascular aortic repair, especially the enhanced risk of late rupture. 17 The study by Patterson et al 12 of the multicenter MOTHER database provides a valuable supplement to the 5-year pivotal trial outcomes for the Talent thoracic stent graft. 15 It seems reasonable to extrapolate the findings of this pivotal trial (n=195) to a much larger cohort of MOTHER patients (n=670).…”
Section: Article See P 24mentioning
confidence: 99%